Efektivitas Layanan Konseling dengan Teknik Kontrak Perilaku Untuk Menurunkan Perilaku Membolos - Hadrawi; Andi Tenri Ampa; Erwin Akib (Prosiding SISFOTEK, 2024)
This study aims to evaluate the effectiveness of counseling services using behavior contract techniques in reducing truancy behavior among students. The behavior contract technique was employed as an intervention to change students' negative behaviors, with the expectation of promoting positive behavior following the implementation of this intervention. The study utilized a pre-experimental design with a one-group pretest-posttest design. The research subjects were eighth-grade students with high levels of truancy behavior, totalling 8 students. Data were collected through questionnaires measuring truancy behavior before and after the intervention. The results showed a significant change in the experimental group after receiving the intervention using the behavior contract technique. The average posttest scores increased significantly compared to the pretest scores, indicating that this technique is effective in reducing truancy behavior. The analysis of independent t-test results also supported this conclusion, as there was a significant difference between the experimental group that received the intervention and the control group that did not receive the intervention. It can be concluded that the behavior contract technique is an effective method for reducing truancy behavior and can be applied as part of counseling services to improve student behavior in schools.